Partial differential equations and boundary value problems with maple V - Articolo, George A. (San Diego Academic Press, 1998)
The book provides many example problems using commands that render two- or three-dimensional animated graphics. The author focuses on the natural union between partial differential equations and a powerful computational language such as Maple.
Keywords: Cơ bản